Fabrication and Performance Analysis of AZO and MCCO as Thin Film-Thermoelectric Generator Materials - Elysa Nensy Irawan; Fahrur Aslami; Aldo Mahendra Putra; Somporn Thaowankaew; Wanatchaporn Namhongsa; Athorn Vora-Ud; Kunchit Singsoog; Tosawat Seetawan4; Melania Suweni Muntini (Universitas Medan Area, 2022)
The purpose of this research was to determine the performance of AZO and MCCO materials as constituents of the thin film-thermoelectric generator module. The method used for fabrication is DC Magnetron Sputtering. The electrode material used is Ag and the substrate used is SiO2 glass. The arrangement of the thin film used for the fabrication of the thermoelectric module is P-N-P-N-P-N-P-N-P-N (5 couples of p-n junctions). Based on the test results, the thickness of the thin film type N is 74.72 nm and type P is 90.34 nm. At the highest test temperature (300 oC), the AZO Seebeck coefficient value is -108 µV/K while the MCCO Seebeck coefficient value is 350 µV/K, and the AZO electrical resistivity value is 0.07 Ω.m while the MCCO electrical resistivity value is 0.36 Ω.m. The highest temperature difference given in the test of the AZO and MCCO thin film thermoelectric module is 1.538 °C and the thermoelectric module can produce a voltage of 1,842 ± 0.047 mV, a Seebeck coefficient of 4 µV/K, and an efficiency of 0.44%. Based on this research, it can be concluded that the performance of AZO and MCCO thin film-thermoelectric modules will have better performance at temperatures around 300 - 350 °C.